ANALISIS SISTEM KEAMANAN HOTSPOT DENGAN MENGGUNAKAN HONEYPOT DAN IDS DI KAMPUS STMIK PPKIA PRADNYA PARAMITA MALANG - Zainuddin, Ahmad; Affandi, Luqman; Duty Susilo, Antonius (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Campus STMIK PPKIA Pradnya Paramita Malang an informatics-based private university in Malang. Security Hotspot used Mikrotik is using a security system. Users who use Hotspot itself is the lecturer and students. Honeypot and IDS is a tool to help security systems that still use Mikrotik Hotspot. Every time there is an attack action using Hotspot then stored into a log of activities each server. Honeypot itself is useful as a shadow Server or Server fake to fool the server where the original moment of the attack. The attack can be done in antaralain Hotspot network using scanning techniques, Arp Spoofing and DDOS. The ultimate goal of this research is to provide a recommendation of Honeypot and IDS analysis results that are tailored to the security system